2016
DOI: 10.1292/jvms.15-0382
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibody to NcSAG1 antigen of <i>Neospora caninum</i> in cattle from Western Java, Indonesia

Abstract: Neospora caninum can cause fetal abortion and neonatal mortality in cattle, and is a cause of economic concern worldwide. This study aimed to determine the prevalence of Neospora caninum-specific antibodies in cattle from Western Java, Indonesia. Serum samples from 991 cattle from 21 locations were tested for antibodies to N. caninum by using an enzyme-linked immunosorbent assay (ELISA) on the basis of recombinant NcSAG1. The overall seroprevalence was 16.6%, ranging from 0 to 87.5% in the sampled locations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We therefore performed a study of the seroprevalence of T. gondii and N. caninum on goat farms in Kanchanaburi province, Thailand. In this study, we used an indirect ELISA with specific recombinant antigen for T. gondii (dense granule protein, TgGRA7) and N. caninum (tachyzoite, NcSAG1), which has previously been used, both by others researchers and also by our working group to investigate specific antibodies against T. gondii and N. caninum in various animal species (Fereig et al, 2016;Ichikawa-Seki et al, 2016;Udonsom et al, 2018). The infection rate of T. gondii (28.5%) in this study is consistent with previous epidemiological studies in Satun province, Thailand that showed 27.9% prevalence (Jittapalapong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore performed a study of the seroprevalence of T. gondii and N. caninum on goat farms in Kanchanaburi province, Thailand. In this study, we used an indirect ELISA with specific recombinant antigen for T. gondii (dense granule protein, TgGRA7) and N. caninum (tachyzoite, NcSAG1), which has previously been used, both by others researchers and also by our working group to investigate specific antibodies against T. gondii and N. caninum in various animal species (Fereig et al, 2016;Ichikawa-Seki et al, 2016;Udonsom et al, 2018). The infection rate of T. gondii (28.5%) in this study is consistent with previous epidemiological studies in Satun province, Thailand that showed 27.9% prevalence (Jittapalapong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Neosporosis seroprevalence in Indonesia has been reported to be 5.80% in Balinese cattle [ 41 ]. Another study in 2015 reported that the neosporosis seroprevalences in West Bandung and Bogor were 26.52% and 30%, respectively [ 42 ]. Our observation revealed 32% and 27.27% seroprevalences in West Bandung and Bogor, respectively.…”
Section: Discussionmentioning
confidence: 99%